Cobalt phthalocyanine as a biomimetic catalyst in the amperometric quantification of dipyrone using FIA - Boni, Ana Carolina [UNESP]; Wong, Ademar [UNESP]; Fireman Dutra, Rosa Amalia; Taboada Sotomayor, Maria Del Pilar [UNESP] (Elsevier B.V., 2011)
A biomimetic sensor for the determination of dipyrone was prepared by modifying carbon paste with cobalt phthalocyanine (CoPc), and used as an amperometric detector in a flow injection analysis (FIA) system. The results of cyclic voltammetry experiments suggested that CoPc behaved as a biomimetic catalyst in the electrocatalytic oxidation of dipyrone, which involved the transfer of one electron. The optimized FIA procedure employed a flow rate of 1.5 mL min(-1), a 75 mu L sample loop, a 0.1 mol L-1 phosphate buffer carrier solution at pH 7.0 and amperometric detection at a potential of 0.3 V vs. Ag/AgCl. Under these conditions, the proposed method showed a linear response for dipyrone concentrations in the range 5.0 x 10(-6)-6.3 x 10(-3) mol L-1. Selectivity and interference studies were carried out in order to validate the system for use with pharmaceutical and environmental samples. In addition to being environmentally friendly, the proposed method is a sensitive and selective analytical tool for the determination of dipyrone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biomimetic catalyst; Cobalt phthalocyanine; Dipyrone; Flow injection system